THE DIFFERENCE IN SPEAKING ABILITY IN LEARNING ENGLISH IN TWO CLASSES AT HIGH SCHOOL - Juhridin (Jurnal Sastra - Studi Ilmiah Sastra, 2025)
This research had the purpose of knowing the different speaking abilities in learning English between class A and class B at the high school. The method that is used by the writer is the Qualitative method, whereas the technique is by distributing questionnaires. This paper consists of five sections. In the first section, the writer analyzes the research material on the problem statement, which includes: 1) How high is the speaking ability learning in English at high school I? 2) How far different is the speaking ability in English at high school I? The second section is the explanation of several theories that have a correlation with the problem statements of this paper. Those are: Learning theory, The function of speaking ability learning, Factors influencing the speaking ability, and the third section, which is entitled Research Methodology, the writer describes the method which was used, the technique, and the instrument of collecting data. In the fourth section, the writer analyzes the data that had been collected and discusses it in the summary of the data collection. Then it suggests some efforts can be done to solve the problem that appears. In the last section, that is chapter V, the writer gives some recommendations related to the problems that appear in section IV. From this research, the writer finds that the differences in speaking ability among male students (class A )in the middle category are because they consider that English is difficult, and it makes the attendance intensity decrease. The speaking ability of female (class B) students is in a good category because they have high motivation and they are more interested in learning English